Novel Three-Dimensional Knitted Fabric for Pressure Ulcer Prevention: Preliminary Clinical Application and Testing in a Diabetic Mouse Model of Pressure Ulcers - Kim, Sungae; Hong, Jamin; Lee, Yongseong; Son, Daegu (Archives of Plastic Surgery, 2022)
Background Population aging has led to an increased incidence of pressure ulcers, resulting in a social burden and economic costs. We developed a three-dimensional knitted fabric (3-DKF) with a pressure-reducing function that can be applied topically in the early stages of pressure ulcers to prevent progression.Methods We evaluated the effects of the 3-DKF in a streptozotocin-induced diabetes mellitus pressure ulcer mouse model, and the fabric was preliminarily applied to patients. Twelve-week-old male C57BL/6 mice were used for the animal experiments. In the pressure ulcer mouse model, an ischemia-reperfusion injury was created using a magnet on the dorsa of the mice. Pressure was measured with BodiTrak before and after applying the 3-DKF to 14 patients at risk of sacral pressure ulcers.Results In the 3-DKF-applied mice group, the ulcers were shallower and smaller than those in the control group. Compared with the mice in the control group, the 3-DKF group had lower platelet-derived growth factor-α and neutrophil elastase expression, as parameters related to inflammation, and increased levels of transforming growth factor (TGF)-β1, TGF-β3, proliferating cell nuclear antigen, and α-smooth muscle actin, which are related to growth factors and proliferation. Additionally, typical normal tissue staining patterns were observed in the 3-DKF group. In the preliminary clinical analysis, the average skin pressure was 26.2 mm Hg before applying the 3-DKF, but it decreased to an average of 23.4 mm Hg after 3-DKF application.Conclusion This study demonstrated that the newly developed 3-DKF was effective in preventing pressure ulcers through testing in a pressure ulcer animal model and preliminary clinical application.
Keywords: diabetes complications; pressure ulcer; streptozotocin; polyesters